Un bolsillo para Corduroy - Freeman, Don, 1908-1978. (New York : Scholastic, 1992)
A toy bear who wants a pocket for himself searches for one in a laundromat.
Translation of: A pocket for Corduroy.
Translation originally published: New York : Viking, c1992.
Keywords: Pockets -- Juvenile fiction; Teddy bears -- Juvenile fiction; Corduroy (Fictitious character); Toys -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Fiction